A review of environmental and health effects of synthetic cosmetics - Wirtu, Yohannes Desalegn (Frontiers in Environmental Science, 2024)
The use of cosmetic products is expanding globally, and with it, so is the range of chemical substances employed in their production. As a result, there is also a higher risk of intoxication, allergic reactions, prolonged chemical exposure, adverse effects, and indiscriminate use. Cosmetic products can contain more than 10,000 ingredients. Most users of synthetic cosmetics are unaware of the harmful effects if they even are. However, it is linked to many diseases like cancer, congenital disabilities, reproductive impairments, developmental systems, contact dermatitis, hair loss, lung damage, old age, skin diseases and reactions, allergies, and harm to human nails. Many beauty products also create a high demand for natural oils, leading to extensive and intensive cultivation, harming natural habitats through deforestation, and contaminating soil and water through pesticides and fertilizers. The adverse effects of hazardous substances in synthetic cosmetics extend beyond human health and influence ecosystems, air quality, and oceans. Thus, this review aims to assess the environmental and health impacts of cosmetics using published scientific articles. The study used a systematic review based on Scopus, Science Direct, Web databases, Scholar Google, and PubMed. The results of this review showed that the formulation of cosmetics until the disposal of their containers could adversely affect environmental and human health.